2017
DOI: 10.1371/journal.pone.0169755
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine Outer Layer Translocation Is Implicated in IL-10 Secretion by Human Regulatory B Cells

Abstract: B cells can have a regulatory role, mainly mediated by interleukin 10 (IL-10). IL-10 producing B cells (B10 cells) cells remain to be better characterized. Annexin V binds phosphatidylserine (PS), which is externalized during apoptosis. Previous works suggested that B10 cells are apoptotic cells since they bind Annexin V. Others showed that Annexin V binding could also be expressed on viable B cells. We aimed to explore if PS exposure can be a marker of B10 cells and if PS exposure has a functional role on B c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Subsequently, it was demonstrated that the mucin domain of TIM-1 was crucial for IL-10 induction by B cells following stimulation with PS-containing apoptotic cells, suggesting a physiologic pathway whereby dying cells promote tolerance to self-antigens and resolution of inflammation by activating IL-10 + TIM-1 + Bregs ( 503 505 ). This proposition is further sustained by observations in mice with a B cell-specific deletion of TIM-1 or mice lacking the mucin domain of TIM-1, which present a profound defect in IL-10 + Bregs and multi-organ tissue inflammation.…”
Section: Tim-1-expressing Bregs (Tim-1 + Bregs)mentioning
confidence: 99%
“…Subsequently, it was demonstrated that the mucin domain of TIM-1 was crucial for IL-10 induction by B cells following stimulation with PS-containing apoptotic cells, suggesting a physiologic pathway whereby dying cells promote tolerance to self-antigens and resolution of inflammation by activating IL-10 + TIM-1 + Bregs ( 503 505 ). This proposition is further sustained by observations in mice with a B cell-specific deletion of TIM-1 or mice lacking the mucin domain of TIM-1, which present a profound defect in IL-10 + Bregs and multi-organ tissue inflammation.…”
Section: Tim-1-expressing Bregs (Tim-1 + Bregs)mentioning
confidence: 99%
“…The start of the apoptotic pathway is characterised by the translocation of phosphatidylserine (PS) from the inner leaflet to the outer membrane and as a result, enables binding of annexin-V to PS [ 30 ]. The annexin-V-FITC positive and PI negative labelled cells were considered as early apoptotic cells and were represented in green on the flow cytometric scattergrams (Fig 5 a, b).…”
Section: Methodsmentioning
confidence: 99%
“…The start of the apoptotic pathway is characterised by the translocation of phosphatidylserine (PS) from the inner lea et to the outer membrane and as a result, enables binding of annexin-V to PS. 29 The annexin-V-FITC positive and PI negative labelled cells were considered as early apoptotic cells and were represented in green on the ow cytometric scattergrams (Fig. 5A-B).…”
Section: Rala/aln Nps Induce Apoptosis and Inhibit The Prenylation Ofmentioning
confidence: 99%